2016
DOI: 10.1016/j.molimm.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing reveals restricted TCR Vβ usage and public TCRβ clonotypes among pancreatic lymph node memory CD4 + T cells and their involvement in autoimmune diabetes

Abstract: Islet-reactive memory CD4(+) T cells are an essential feature of type 1 diabetes (T1D) as they are involved in both spontaneous disease and in its recurrence after islet transplantation. Expansion and enrichment of memory T cells have also been shown in the peripheral blood of diabetic patients. Here, using high-throughput sequencing, we investigated the clonal diversity of the TCRβ repertoire of memory CD4(+) T cells in the pancreatic lymph nodes (PaLN) of non-obese diabetic (NOD) mice and examined their clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 69 publications
(118 reference statements)
1
19
0
Order By: Relevance
“…The TCRb CDR3 regions were amplified and sequenced from sorted CD8aa T unc and CD8 T con from liver MNCs of naive B6 mice or from human PBMC. Amplification and sequencing of TCRb CDR3 regions were performed on the ImmunoSEQ platform at Adaptive Biotechnologies (Seattle, WA) as previously described (24). Sequences that did not match CDR3 sequences were removed from the analysis.…”
Section: High-throughput Sequencing Of the Tcr Genesmentioning
confidence: 99%
“…The TCRb CDR3 regions were amplified and sequenced from sorted CD8aa T unc and CD8 T con from liver MNCs of naive B6 mice or from human PBMC. Amplification and sequencing of TCRb CDR3 regions were performed on the ImmunoSEQ platform at Adaptive Biotechnologies (Seattle, WA) as previously described (24). Sequences that did not match CDR3 sequences were removed from the analysis.…”
Section: High-throughput Sequencing Of the Tcr Genesmentioning
confidence: 99%
“…Autoreactive T cell clones bearing distinct TCR Vβ chains expand in the target organs of autoimmune disease. For instance, T cells of the Vβ8.2 family recognizing MOG 35–55 are predominant in the brain of C57BL/6 mice ( 47 ), and the repertoire of T cells infiltrating the pancreas of the NOD mouse is skewed to a limited set of families, including Vβ2, Vβ4, Vβ6, Vβ8.1, and Vβ12 ( 37 41 , 56 ). Interestingly, injection of dexamethasone in the first 3 days of life has been shown to exert long-lasting effects on the expression of several Vβ genes in rats ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marrero et al identified islet antigen-reactive TRBV13-2 (Vβ8.2) public clones from the pLN of NOD mice. Importantly, a tolerogenic vaccine composed of an immunodominant peptide that binds the TCR Vβ8.2 chain prevented T1D in NOD mice [ 47 ] supporting the notion that public TCRs may serve as biomarkers and potential therapeutic targets. Currently, autoantibodies represent the best available biomarker to predict human T1D onset.…”
Section: Tcrs As Biomarkersmentioning
confidence: 98%